Rancang Bangun Sistem Pemantauan Infus dan Tekanan Darah pada Pasien Rawat Inap secara Real Time - Vera Veronica -; Rahmadi Kurnia - (Jurnal Ilmiah Poli Rekayasa, 2017)
The problems that often arise in inpatients, especially those that need special handling such as infusion fluids should be given is often the occurrence of negligence in the infusion bottle examination is good condition of fluids in infusion bottles and the number of droplets per minute that is not appropriate. In addition, the patient will also be disrupted when the nurse should take care of the patient's blood pressure periodically. To overcome these problems need to be made a system that can monitor all of it in real time.This system design process requires a hardware and software that is integrated in such a way that it can be used to monitor the infusion and blood pressure of the patient. The main hardware required is the infrared sensor and the pressure sensor where the sensor will be controlled by the microcontroller device which the results can be sent to the monitoring computer wirelessly.           From the overall testing of the design that has been made, it can generally be applied but there are still shortcomings that occur in measuring instruments, especially blood pressure gauges where the average error occurred in the measurement of systolic pressure of 8.42% and the average error that Occurs in diastolic measurements of 4.90% and on data delivery there is a significant delay spike when given a barrier.